Strategi Komunikasi Pembina Rumah Qur’an Al-Irsyad Dalam Meningkatkan Minat Santri Penghafal Al-Qur’an Di Kanagarian Taeh Bukik Kabupaten Lima Puluh Kota - Yusro, Lailatul; Ahmad, Fajri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2025)
The Al-Irsyad Qur’an House is a non-formal educational institution that focuses on learning, memorizing, and practicing the Qur’an within the community. The issue underlying this research is the lack of interest among some students in memorizing the Qur’an at the Al-Irsyad Qur’an House. Therefore, it is necessary to implement appropriate communication strategies by the instructors to increase the students’ interest and motivation. The purpose of this study is to identify and understand the forms of communication strategies used by the instructors of the Al-Irsyad Qur’an House to foster students’ interest in becoming Qur’an memorizers (ḥuffāẓ). This research uses a qualitative descriptive method, while data collection techniques include interviews, observation, and documentation of relevant materials. The study examines how the instructors apply communication strategies to enhance students’ interest by employing the Compliance-Gaining Strategy, Constructivism Theory, and Politeness Strategy Theory. Based on the findings, the instructors at the Al-Irsyad Qur’an House implement three main strategies to improve the students’ interest in memorizing the Qur’an. First, the Compliance-Gaining Strategy is applied through providing motivation, guidance, as well as implementing rewards and sanctions that encourage students to be more disciplined in maintaining their memorization. Second, the Constructivism Strategy is realized by adjusting communication methods according to each student’s character and ability, ensuring that every message is well received and fosters deeper understanding. Third, the Politeness Strategy is applied to maintain ethical communication among instructors, students, and parents, thereby creating a harmonious relationship and a conducive learning atmosphere. These three strategies complement one another in enhancing the students’ motivation and enthusiasm in their Qur’an memorization activities.